Dinamika Kajian al-Quran di Pondok Pesantren: Studi Kasus Kajian al-Quran di Pondok Pesantren An-Nur Ngrukem Bantul Yogyakarta pada tahun 1978-2018 M - Dewi Ayu Kusuma Ning Tyas (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2022)
This study discusses the origin, change and continuity as well as the factors causing the study of the Qur'an at An-Nur Ngrukem Islamic Boarding School. It is qualitative research oriented towards literature study and oral history. The approach used is historical with heuristic methods, source criticism, interpretation and historiography. The results of the study, namely the study of the Qur'an at the An-Nur Ngrukem Islamic boarding school from 1978 AD to 2018 AD, did not change much. At the beginning of the establishment of the An-Nur Ngrukem Islamic boarding school, there was only a study of tahsin (qir?'ah Ashim) and tahfid then a study of commentaries and other classical books such as the Madrasah Diniyah Al-Furqon. The teaching system, facilities and infrastructure developed and the An-Nur Qur'an Education Park (TPQ) institution was established which was devoted to the children of the Ngrukem hamlet and its surroundings using the yanbu'a method. And the pioneering of qir?'ah sab'ah guidance for students who have memorized 30 juz. This was followed by the establishment of educational institutions to support the formal education of the students.